Distorsi Komunikasi Pembangunan Pemerintahan Presiden Jokowi di Media Sosial - Jaya, Pajar Hatma Indra (FISIP Universitas Atma Jaya Yogyakarta, 2017)
Jokowi’s image as a leader is populist-nasionalist. However, there were some contradictory news with the related image in the social media, which is released in December 2016 until January 2017. This research aims to explore those distorted news. It is revealed that the government media framing did not dominate the social media. The news were interpreted or added in accordance with the viewer’s interest that leads to a hoax. This research reinforces Barthes, Baudrillard, and Eco that the era of social media brings the death of reality.